The Influence of Banyumas Promotional Themes on Engagement Levels on TikTok in 2025 - Ikhwani, Dimas; Wibowo, Afiya Sari; Zahrah, Aulia; Rahmani, Mastika; Pane, Bayhaqi Adriansa; Wahono, Illona Tisha Nathania; Ramadhani, Amalia Nur (Jurnal Ilmiah WUNY, 2026)
Background: Social media, particularly TikTok, has emerged as a significant instrument in digital marketing communication strategies and regional promotion campaigns in Indonesia. Objectives: This study aims to analyze the influence of promotional themes—tourism, culture, and culinary—on the engagement rate of Banyumas Regency's promotional content on the TikTok platform in 2025. Method: This study employed Quantitative Content Analysis with a population comprising all Banyumas promotional content uploaded during the period of January 1 to August 30, 2025. A total of 165 samples were selected using a simple random sampling technique. Data collection was conducted through non-participatory observation with systematic coding using a coding sheet. Data analysis was performed using descriptive statistics and inferential testing through One-Way ANOVA. Result: Findings indicate that culture-themed content achieved the highest engagement rate (1.39), followed by tourism-themed content (1.28) and culinary-themed content (1.27). The ANOVA test yielded a significance value of 0.429 (> 0.05), indicating that the influence of promotional themes on engagement rate is statistically not significant. Conclusion: TikTok engagement performance is not primarily determined by thematic substance but rather by the degree to which content aligns with the platform's algorithmic logic. Therefore, regional promotion efforts through TikTok should prioritize content creativity, production quality, and stylistic adaptation to platform norms over mere thematic selection.